LAYANAN BIMBINGAN KELOMPOK TENTANG KONSEP DIRI PESERTA DIDIK KELAS VII SMP NEGERI 7 SUNGAI RAYA - Fransiska Sarbina; M. Asrori; Indri Astuti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractSelf- concept is an argued of people from what we think, about ourselves, and what we are desired.  The guidance of the group means an activity can also support educated participants in developing potential, and they can take benefits from learning experience to itself through a group. Therefore, this study aimed to know about participants’ self-concept through the guidance of the group at SMP Negeri 7 Sungai Raya. This research used quantitative as a design, the researcher also used descriptive method and study survey to this research. The technical technique used an indirect communication techniques. The participant were 60 participants of the seventh grade at SMP Negeri 7 Sungai Raya.  The study found that participants’ self concept through the guidance of the group with the actual score 3306 and the ideal score 3600 with range precentage 92% in category “high”.Keywords: Self-Concept, The Guidance Of The Group